PTFE-Activated Graphene Overcomes Dispersion Challenges for Scalable Solvent-Free Fabrication of Ultra-Thick, High-Performance Cathodes in Lithium Metal Batteries - Yoon, Juhee; Kang, Dong Hyuk; Shin, Sangmin; Yoo, Suhyoung; Kim, Hyemin; Lee, Jin-kyun; Jin, Hyoung-joon; Yun, Young Soo (John Wiley & Sons Ltd., 2026)
Dry-processed ultra-thick cathodes can boost energy density through process innovation alone, but face key challenges from nonuniform additive/binder dispersion and increased ion-transport resistance with thickness. In this study, a reduced graphene oxide (rGO)-based nanocomposite in which polytetrafluoroethylene (PTFE) nanoparticles are anchored onto rGO surfaces is introduced. This PTFE anchoring effectively prevents graphene restacking and enables uniform dispersion throughout the electrode during the solvent-free fabrication process via in situ nanofibrillation of PTFE. By employing this rGO@PTFE nanocomposite as a dual-functional conductive and binding material, we successfully fabricated a high-energy cathode based on high-nickel layered oxide (NCM), achieving a significantly high areal and volumetric capacity of 15.2 mA h cm-2 and 562.9 mA h cm-3, respectively. The incorporation of rGO@PTFE led to improved electrolyte wettability and uptake, as well as enhanced electronic conductivity. More importantly, it raised the lithium-ion transference number to 0.73 and reduced the charge transfer resistance by 62% compared to a conventional reference electrode. Based on these advantages, the rGO@PTFE-based thick cathode (G@P_TC), when paired with a lithium metal anode, enabled the development of a lithium metal battery with an unprecedented high volumetric energy density of 1088 Wh L-1, while maintaining nearly 92% capacity retention over 50 cycles.